KONDISI FISIK SEPAK BOLA U-15 PADA SSB IMAM BONJOL KOTA PADANG - M Fadhli; Yanuar Kiram; Vega Soniawan; Bram Sujadesman (JURNAL ILMU KEOLAHRAGAAN, 2026)
Physical condition plays a crucial role in supporting soccer players’ performance, especially among young athletes who are still in their developmental phase. However, to date, there has been no clear data regarding the physical condition of the U-15 players at SSB Imam Bonjol in Padang. This study aims to determine the physical fitness levels of U-15 soccer players from SSB Imam Bonjol in Padang, including: endurance, speed, agility,  power, and coordination. The study employed a descriptive research design using a quantitative approach, with calculations based on percentages. The sample size for this study was 41 players. The results indicate that endurance falls into the average/adequate category, while explosive power and speed are in the good category, and agility and coordination are in the very good category. Based on these results, it can be concluded that the physical condition of U-15 soccer players at SSB Imam Bonjol in Padang is generally in the “Good” category. Therefore, it is recommended that coaches design training programs that strike a better balance between technique, tactics, and physical conditioning to achieve even better results.